Evaluation of popular drug information resources on clinically useful and actionable pharmacogenomic information - Jennifer S. Chang; Duyen-Anh Pham; Maithao T. Dang; Yiting Lu; Sheri VanOsdol; Jaekyu Shin (Journal of the Medical Library Association, 2016)
Background: Pharmacogenomics is the study of how genes affect a person’s response to drugs. This descriptive study assessed whether popular drug information resources provide clinically useful pharmacogenomic (PGx) information.